Post-conflict reconstruction and the heritage process. Issue 2 (4th May 2018) - Legnér, Mattias
ABSTRACT: Despite that large investments have been made by the European Union in restoring and preserving heritage damaged after the Kosovo War 1998–99, there have been no previous attempts to gain more in-depth knowledge about the implementation and success of the interventions. Organisations involved in funding and facilitating architectural interventions in post-conflict zones may have differing aims and agendas that influence selection and methods, and ultimately the results. This paper aims to shed light on a pioneering project carried out on damaged kullas, massive masonry towers connected to farmsteads, in Kosovo 2001–02. Kullas were systematically attacked and burned during the conflict. The methodology is based on interviews with involved people and on documentation that is publically available, since it is crucial to uncover the aims and agendas of involved actors if one wishes to understand how and why decisions were made. In the end, what was deemed most important in the process was not the reconstruction in itself, but rather the development of craftsmen's skills and the need to create a dialogue on the values of Kosovo heritage. The paper shows how the reconstruction of built heritage can facilitate processes of dialogue in conflict areas.